Evaluation of Bicycle Transportation Experiences and Bicycle Planning in Turkey, Land Use – Praxis Based Model Proposal - Hatice Gül Önder; Furkan Akdemir (Journal of Transportation and Logistics)
Today, the bicycle is one of the best-accepted means of transport modes of the world within the framework of sustainability. The effort which governments make to make bicycle transport widespread has been formed through making plans for bicycle transportation and carrying them out in the physical environment. In this study, the lawful framework for bicycle use and its regulations in Turkey, and regulations about bicycle transport planning of some cities whose transportation master plans have been analyzed. As a result of the examinations made, the proposal of a bicycle transport planning model based on the land use-transportation-praxis trio has been improved. This proposal defines the advancement of the bicycle transportation network from immediate surroundings to farther, larger-scale land use, primarily from the praxis of bicycling of people as a hobby to more comprehensive demands in which bicycle use is needed to go to work. It has been concluded that according to the developed model, while the activity of cycle transport planning is made in new areas, bicycle transport praxis of the residents, as in the model, should be organized in coordination with land use and in the framework of preparation> organizing>moving stages.